2017
DOI: 10.1016/j.dld.2017.09.087
|View full text |Cite
|
Sign up to set email alerts
|

Functional chronic constipation: Rome III criteria versus Rome IV criteria

Abstract: Background/AimsFunctional constipation (FC) is aa frequent functional gastrointestinal disorder, diagnosed according to the Rome criteria. In this study, we compared Rome III and Rome IV criteria for the diagnosis of FC, and determined the prevalence of FC according to these criteria. MethodsConsecutive children between infancy and 17 years old were recruited for the study, excluding those with a known organic gastrointestinal disease. A prospective longitudinal design has beenused. For the diagnosis of FC, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…Our findings contrast with studies from other countries that also used the Rome IV criteria and reported a lower prevalence of FC (12% United States; 13.6% Italy). 10,11 This suggests that changes in the Rome IV criteria (compared to the Rome III criteria) in this age group did not modify the overall prevalence of FC and that the prevalence of FC seems to vary among regions.…”
Section: Discussionmentioning
confidence: 78%
“…Our findings contrast with studies from other countries that also used the Rome IV criteria and reported a lower prevalence of FC (12% United States; 13.6% Italy). 10,11 This suggests that changes in the Rome IV criteria (compared to the Rome III criteria) in this age group did not modify the overall prevalence of FC and that the prevalence of FC seems to vary among regions.…”
Section: Discussionmentioning
confidence: 78%
“…The QPGS-IV has been used to estimate the prevalence of FGIDs in multiple studies in children. 1,5 Studies comparing the prevalence of FGIDs in children using the Rome III and Rome IV criteria have shown differences in prevalence predominantly in abdominal migraine, irritable bowel syndrome (IBS), and functional dyspepsia. 1,2 It is important to understand if those differences resulted from modifications of the Rome criteria or innate errors in measures.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to these American reports (21) and previous Mediterranean work, in our present population, the most frequent FGID in both age groups was FC, with a prevalence ranging between 7.46% in children to 13.7% in adolescents. In the youngest group, FC was significantly less identified with Rome IV criteria in the Mediterranean area although in the previous report its prevalence (11.7%) was higher compared with other studies (2,19,22). In a recent systematic review and meta-analysis of studies using comparable methodology and all iterations of the Rome criteria, the pooled prevalence of FC was 15.3% (95% CI 8.1–24.4; I 2 = 99.4%) in studies using the Rome I criteria, 11.2% (7.9–14.9; I 2 = 99.6%) in studies that used Rome II criteria, 10.4% (6.5–14.9; I 2 = 99.8%) in those that used Rome III criteria, and 10.1% (8.7–11.6; I 2 = 98.2%) when Rome IV criteria were used.…”
Section: Discussionmentioning
confidence: 78%